Abracadabra Trumpet : The Way to Learn Through Songs and Tunes - Tomlinson, Alan (London A & C Black, 2008)
"The perfect book for pupil and teacher - songs and tunes you will know and want to play, carefully graded to cover each aspect of technique for the beginner"--Publisher's description.
Include Illustrations and Index
Keywords: Trumpet -- Trumpet--Instruction and study -- Trumpet music -- Teaching pieces